ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NON PERFORMING LOAN (Studi Pada Bank Umum Konvensional Go Public Di Indonesia Periode 2010-2014) - Wardhana, Galih Wisnu; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2015)
Conventional commercial bank is vulnerable hit by Non Performing Loans (NPL) because credit as the main source of income comes from a conventional bank Although the bank’s management had made efforts based on the credit rating of 5C+1C but still the banks potentially exposed tho tb he credit risk The purpose of this research was to know how big the influence of variable CAR, LDR, BANK SIZE, ROA, and BOPO, against Non Performing Loan (NPL) in Conventional commercial banks go public in 2010-2014.This research was conducted with purposive sampling. The samples used were 25 conventional commercial banks go public in Indonesia. The data used in this research are the Annual Report of each bank in 2010-2014 were obtained from Bloomberg, the official website of Indonesian Stock Exchange (IDX), and the official website of Bank Indonesia.. This research uses multiple linear regression analysis as data analysis tools.Based on the test for normality, multicollinearity test, heteroskedastisitas test and autocorrelation test, there were no deviations from goodness of fit. This indicates that the available data has been qualified to use the model of multiple linear regression equation. From the analysis indicates that CAR, LDR, ROA have no significance effect on NPL, Whereas Bank Size and ROA have significant influence on the NPL. Predictive capabilityof the five variables to Non Performing Loan (NPL) of 29%, while the remaining 71% influenced by other factors not included in the research model.